Nuts and bolts : strengthening the inner circle for environment and sustainable development : the case of the Caribbean Community - Griffith, Mark D. (Caribinvest Publishing St. MichaelBB, 2009)
Aims to address the environmental, natural resources management and sustainable development challenges which confront the Caribbean Community and suggests a radically different approach than the one adopted over the last three decades to resolve these issues.